On the Special Conceptual Framework for the Fire Forensics - I. S. Taubkin (Теория и практика судебной экспертизы)
The article addresses the issues of the particular terminology for fire forensic investigations. Definitions for the basic parameters of a fire hazardous area, determining its susceptibility to ignition, and their relationship to the impulses initiating such areas’ combustion are analyzed.Two main tasks of forensic fire examinations are reviewed: establishing the technical cause of a fire, its organizational cause, and consequences. The author gives definitions for these tasks and the term “ignition source”.The paper’s relevance stems from the need to prevent mistakes in terminology when conducting a forensic fire investigation. The article may be of use for practicing experts and specialists in fire forensics’ theory and practice.